A Point Source Identification Problem for a Time Fractional Diffusion Equation. (8th December 2013) - Yang, Xiao-Mei; Deng, Zhi-Liang
Abstract : An inverse source identification problem for a time fractional diffusion equation is discussed. The unknown heat source is supposed to be space dependent only. Based on the use of Green's function, an effective numerical algorithm is developed to recover both the intensities and locations of unknown point sources from final measurements. Numerical results indicate that the proposed method is efficient and accurate.